Effectiveness of the salt therapy - current knowledge status - Paulina Oleksa; Piotr Więsyk; Karol Spozowski; Piotr Wójcik (Kazimierz Wielki University, 2022)
Introduction: The salt therapy is a form of the aerosol therapy using sodium chloride in different forms. The beginnings of the halotherapy date back to the nineteenth century when it has been practised as a medical treatment in the old salt mines of Central and Eastern Europe. The salt therapy as an adjuvant method seems to have positive impact on treatment of respiratory system diseases and dermatological conditions. We distinguish two types of the dry salt therapy: halotherapy and speleotherapy. Purpose of the article: We aimed to evaluate efficacy of the salt therapy in treatment of pulmonary and dermatological disorders. Material and methods: We searched three electronic databases: Pubmed, Web of Science and Google Scholar from inception to the August 2022 and conducted a review. The following descriptors were used: "halotherapy", "speleotherapy" and "salt therapy". Results and conclusions: The salt therapy improves mucociliary elimination, pulmonary functions and reduces airway's irritation. It also reduces intensity of the dryness, redness and stimulates regenerative processes in the skin. This method is safe and do not cause the serious adverse effects. Therefore, due to its potential benefits, it should be considered as an additional therapy beside standard treatment procedures inter alia in the asthma, chronic obstructive pulmonary disease, psoriasis, atopic dermatitis. Moreover, halotherapy has positive impact on children's general development as it enhances the growth and weight gain. However, scientific evidences for effectiveness of the salt therapy are limitted. There is a need of further studies assessing effectiveness of the long-therm salt therapy on the larger group of patients.